The Theories of Principles in Deep Learning Approach: Teori-Teori dalam Prinsip-Prinsip Pendekatan Pembelajaran Mendalam - Rosyidah, Ferdiana; Parmiti, Desak Putu; Sanjaya, Dewa Bagus; Jampel, I Nyoman (Universitas Muhammadiyah Sidoarjo, 2026)
Deep learning is an approach that launched by the Ministry of Primary and Secondary Education with an academic manuscript that can be viewed freely on its page. It has three main principles, that are mindful, meaningful, and joyful that should be implemented simultaneously during the learning process. This article discussess the theories of these three main principles from various figures such as Langer, Ausubel, and Dewey by using the literature study from various articles and books. The discussion of this article is designed to help educators more understand about the core of the approach accompanied by practical examples, enabling them to align the learning process with national policies. The principles in deep learning are aligned with constructivism theory, which made students as active subjects in the learning process. Students are aware of the leraning objectives and fully engaged in learning activities which the content is connected to real-life experiences, enabling them for constructing the conceptual knowledge. This article focuses solely on constructivism theory despite the existence of other theories that also support educational innovation. Highlights: Three interconnected principles frame a holistic student-centered approach grounded in awareness, cognitive integration, and experiential engagement. The framework positions learners as active knowledge constructors through contextual instruction and structured conceptual organization. Practical classroom strategies include initial assessment, project-based activities, and reflective interaction aligned with national curriculum policy. Keywords: Deep Learning, Mindful, Meaningful, Joyful